The Relationship Between Hope, Career Identity, And Job Satisfaction With Turnover Intention In Nurses At Hospital X - Sri Hastuti; Siswanto Pabidang (International Journal of Health Engineering and Technology, 2026)
The increasing tendency of nurses to leave their jobs (turnover intention) has become a critical issue for hospitals, as it may affect service quality and the sustainability of human resources. This concern becomes more prominent when turnover rates exceed the normal range of 5–10% per year. Individual psychological factors, such as hope, career identity, and job satisfaction, are assumed to influence this condition. This study aims to examine the relationship between these factors and turnover intention among nurses at Hospital X. A quantitative study with a cross-sectional design was conducted in 2025. A total of 104 nurses were included as respondents using a total sampling technique. The variables analyzed were hope, career identity, job satisfaction, and turnover intention, measured using structured questionnaires. Data were analyzed using Pearson correlation to assess the relationships between variables. The findings revealed that all independent variables were significantly associated with turnover intention (p < 0.001). Among them, career identity demonstrated the strongest relationship. All variables showed a negative correlation, indicating that higher levels of hope, career identity, and job satisfaction were associated with lower turnover intention among nurses. Hope, career identity, and job satisfaction are significantly related to turnover intention among nurses. Therefore, hospitals are encouraged to strengthen psychological aspects and improve job satisfaction as part of strategies to reduce turnover intention and enhance nurse retention.